Multiportal vs. uniportal video-assisted thoracoscopic lobectomy: a critical overview - Perna, Valerio (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
The advent of uniportal video-assisted thoracoscopic lobectomy (uniportal VATS lobectomy) has enlivened the worldwide thoracic surgery community over the last five years. This approach promised the least access trauma of any VATS lobectomy technique thus far (1), but it is striking that the promoters of this technique have not endeavoured sufficiently to prove its hypothetical advantage.